Direct rate-constant measurements and theoretical insight into the mechanism of the reactions H + hexamethyldisiloxane and H + tetramethyldisiloxane*. (17th September 2021) - Somnitz, H.; Peukert, S.; Schäffer, R.; Fikri, M.; Schulz, C.
ABSTRACT: Shock-tube experiments were conducted to determine rate-coefficient data of the H-atom abstraction reactions H + HMDSO (hexamethyldisiloxane) → H2 + HMDSO−H and H + TMDSO (tetramethyldisiloxane) → H2 + TMDSO−H . The experiments comprised a temperature range of 1109–1240 K and pressures between 1.2 and 1.5 bar. In all experiments, C2 H5 I was used as a precursor for H atoms. H-atom concentrations were measured with atomic resonance absorption spectrometry (ARAS) and rate-coefficient data were obtained from pseudo-first-order analysis of temporal H-atom concentration profiles. Experimental total rate-coefficients were well represented by the following Arrhenius equations: k total, HMDSO ( T ) = 10 −9.49±0.36 exp(−32.4 ± 8.1 kJmol −1 / RT ) cm 3 molecule −1 s −1 for H + HMDSO and k total, TMDSO ( T ) = 10 −8.00±0.36 exp(−53.3 ± 7.9 kJ mol −1 / RT ) cm 3 molecule −1 s −1 for H + TMDSO. Multiple reaction channels were explored by computations at G4//B3lyp-D3BJ level of theory. GRAPHICAL ABSTRACT: UF0001